The Antinomy of Being - Harries, Karsten (De Gruyter, 2019)
One thing this book attempts to show is that Kant's antinomies open a way towards an overcoming of that nihilism that is a corollary of the understanding of reality that presides over our science and technology. But when Harries is speaking of the antinomy of Being he is not so much thinking of Kant, as of Heidegger. Not that Heidegger speaks of an antinomy of Being. But his thinking of Being leads him and will lead those who follow him on his path of thinking into this antinomy. At bottom, however, the author is neither concerned with Heidegger's nor Kant's thought. He shows that our thinking inevitably leads us into some version of this antinomy whenever it attempts to grasp reality in toto, without loss. All such attempts will fall short of their goal. And that they do so, Harries claims, is not something to be grudgingly accepted, but embraced as a necessary condition of living a meaningful life. That is why the antinomy of Being matters and should concern us all.